The evolving landscape of anatomic pathology. (October 2022) - Pisapia, Pasquale; L'Imperio, Vincenzo; Galuppini, Francesca; Sajjadi, Elham; Russo, Alessandro; Cerbelli, Bruna; Fraggetta, Filippo; d'Amati, Giulia; Troncone, Giancarlo; Fassan, Matteo; Fusco, Nicola; Pagni, Fabio; et al.
Abstract: Anatomic pathology has changed dramatically in recent years. Although the microscopic assessment of tissues and cells is and will remain the mainstay of cancer diagnosis molecular profiling has become equally relevant. Thus, to stay abreast of the evolving landscape of today's anatomic pathology, modern pathologists must be able to master the intricate world of predictive molecular pathology. To this aim, pathologists have had to acquire additional knowledge to bridge the gap between clinicians and molecular biologists. This new role is particularly important, as cases are now collegially discussed in molecular tumor boards (MTBs). Moreover, as opposed to traditional pathologists, modern pathologists have also adamantly embraced innovation while keeping a constant eye on tradition. In this article, we depict the highlights and shadows of the upcoming "Anatomic Pathology 2.0" by placing particular emphasis on the pathologist's growing role in the management of cancer patients. Graphical Abstract: ga1 Highlights: Anatomic pathology has changed dramatically in recent years. Molecular profiling has become equally relevant to microscopic evaluation in modern Anatomic Pathology. Modern pathologists must be able to master the intricate world of predictive molecular pathology. This new role is particularly important, as cases are now collegially discussed in molecular tumor boards.